Analysis of Kinderflix Video Animation Content and Parents' Responses to the YouTube Platform as a Source and Media for Learning Indonesian for Babies and Toddlers - Antika, Cindy Dwi; Simanjuntak, Nensy Megawati (PT FORMOSA CENDEKIA GLOBAL, 2024)
Using animated video content is a form of learning media because it can help gain values and perspectives. By providing audio-visual content that children consume, children will have a positive and enjoyable learning experience. This research explains that the YouTube platform can be a source and teaching medium using animation and audiovisuals. This study aims to introduce the use of Kinderflix video animation content on the YouTube platform as a source and medium for learning Indonesian for infants and toddlers. It can be concluded from the current research that the use of the YouTube platform as a learning resource and medium can help toddlers to show responses from educators/parents as well as babies and toddlers to the learning content on the Kinderflix YouTube account. The current research topics can provide valuable learning experiences and help parents in the process of children's development stages.